2014
DOI: 10.3390/app4020305
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Properties of Graphene for Interconnect Applications

Abstract: A semi-classical electrodynamical model is derived to describe the electrical transport along graphene, based on the modified Boltzmann transport equation. The model is derived in the typical operating conditions predicted for future integrated circuits nano-interconnects, i.e., a low bias condition and an operating frequency up to 1 THz. A generalized non-local dispersive Ohm's law is derived, which can be regarded as the constitutive equation for the material. The behavior of the electrical conductivity is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…Multilayered graphene, which can be produced on a large scale, shows excellent performance, especially on thermal conductivity and mechanical stiffness [25][26][27][28]. It is widely used in sensors [29], electrodes [30,31], and other areas [32,33]. For example, Johnson et al reported a fabrication method for hydrogen sensing using a multilayered graphene, which opened up the possibility of using multilayered graphene in molecular sensing applications [29].…”
Section: Introductionmentioning
confidence: 99%
“…Multilayered graphene, which can be produced on a large scale, shows excellent performance, especially on thermal conductivity and mechanical stiffness [25][26][27][28]. It is widely used in sensors [29], electrodes [30,31], and other areas [32,33]. For example, Johnson et al reported a fabrication method for hydrogen sensing using a multilayered graphene, which opened up the possibility of using multilayered graphene in molecular sensing applications [29].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the basic components of carbon electronics will consist of quasi-one-dimensional graphene structures that graphene nanoribbons essentially are. Today, researchers are working on the theoretical and experimental studies of their application as passive elements, namely interconnectors [7,8], waveguides [9,10], and dividers [11]. They also pay attention to the active elements of electronic circuits, such as amplifiers and switches [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…As alternative conductor materials, carbon nanomaterials, including carbon nanotubes (CNTs) and graphene, have aroused lots of interest due to their outstanding physical properties [3][4][5][6][7][8][9]. According to the number of carbon atom layers in a CNT wall, CNTs can be classified into single-walled CNTs (SWCNTs) and multi-walled CNTs (MWCNTs).…”
Section: Introductionmentioning
confidence: 99%